The Role Of Islamic Religious Education Teacher In Creating Anti-Corruption Generation - Asroni, Ahmad (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This article describes the strategic and important role of Islamic Religious Education (IRE) teachers in creating anti-corruption generation. There are several things that IRE teachers should pay attention in the implementation of anti-corruption education. First, understanding and mastery of anti-corruption educational materials. Second, the ability of IRE teachers to design interesting methods and media of anti-corruption education learning. Third, the anti-corruption education learning model conducted by IRE teachers should not only emphasize the cognitive aspect, but also the affective and psychomotor aspects. Fourth, in evaluating student learning outcomes should not only be based on cognitive or intellectual abilities but should also be based on the attitudes and behaviors of students.